Nonlinear guidance and fuzzy control for three-dimensional path following of an underactuated autonomous underwater vehicle - Yu, Caoyang; Xiang, Xianbo; Lapierre, Lionel; Zhang, Qin (Ocean engineering, 2017)
This paper proposes a simplified nonlinear fuzzy controller integrating an improved three-dimensional (3D) guidance law, in order to address the problem of path following for an underactuated autonomous underwater vehicle (AUV) exposed to unknown environmental disturbances. First, an improved 3D line-of-sight guidance law that makes full use of the essentially equivalent coordinate transformation is derived to transform 3D path following position errors into controlled guidance speeds, which also reduces the path following system form second-order to first-order. The side-slip angle and angle of attack are integrated into 3D guidance design to account for the underactuated configuration in sway and heave. Second, a nonlinear single-input fuzzy controller is designed to reduce computation complexity resulting from square rules in a double-input fuzzy controller, and to force the steerable speeds of an AUV to attain their guidance profiles. Subsequently, sensitivity analysis is adopted to suggest that the nonlinear fuzzy design with the convergent distribution and small slope for the single input have better robustness against unknown disturbances than the linear design. Finally, numerical examples with quantitative comparison are provided to illustrate the performance of the nonlinear single-input fuzzy controller for 3D path following of an underactuated AUV exposed to unknown environmental disturbances. •An improved guidance law transforms 3D path following errors into controlled speed errors.•A simplified nonlinear single-input fuzzy controller against unknown disturbances is designed.•Sensitivity analysis suggests that the nonlinear single-input fuzzy design have better robustness.•Numerical examples validate the robust performance of the whole control system.